War and love: Ye Chuanhua (Diep Truyen Hoa) and his war time poems - Ken, D.W.T.; Wah, F.P.; Ling, C.S. (Central China Normal University, 2014)
The literary world of the ethnic Chinese in Vietnam was once a thriving community that produced a wide range of works pertaining to the community. These works were represented through the various genres of literatures including novel, short stories, prose and poetry. The community had a constant supply of new members as the Chinese in Vietnam maintained its own school system which continued to produce students who were receptive to the idea of having their own Vietnamese Chinese literature. The existence of local Chinese newspapers was yet another impetus to the development of Chinese literature in Vietnam. But the development of this category of literature came to an end with the fall of Saigon to the North Vietnam army in April 1975. This paper will look into the last works by a prominent Vietnamese Chinese educator by the name of Ye Chuanhua (Diep Truyen Ha), whose last three poems may represent the crucial times he lived through, and the exasperation he felt in a situation beyond his control, especially as an ethnic Chinese in an increasingly nationalistic country, and finally, his feelings for his wife at the time when he was suffering from terminal sicknesses.